Philosophies and practices of emancipatory nursing social justice as praxis - Kagan, Paula N.; Smith, Marlaine C.; Chinn, Peggy L. (Routledge studies in health and social welfare, 2014)
"This anthology presents the philosophical and practice perspectives of nurse scholars whose works center on promoting nursing research, practice, and education within frameworks of social justice and critical theories. Social justice nursing is defined by the editors as nursing practice that is emancipatory and rests on the principle of praxis which is practice aimed at attaining social justice goals and outcomes that improve health experiences and conditions of individuals, their communities, and society. There is a lack in the nursing discipline of resources that contain praxis approaches and there is a need for new concepts, models, and theories that could encompass scholarship and practice aimed at purposive reformation of nursing, other health professions, and health care systems. Chapters bridge critical theoretical frameworks and nursing science in ways that are understandable and useful for practicing nurses and other health professionals in clinical settings, in academia, and in research. In this book, nurses' ideas and knowledge development efforts are not limited to problems and solutions emerging from the dominant discourse or traditions. The authors offer innovative ways to work towards establishing alternative forms of knowledge, capable of capturing both the roots and complexity of contemporary problems as distributed across a diversity of people and communities. It fills a significant gap in the literature and makes an exceptional contribution as a collection of new writings from some of the foremost nursing scholars whose works are informed by critical frameworks"..